2012
DOI: 10.4161/cc.21465
|View full text |Cite
|
Sign up to set email alerts
|

pH neutralization protects against reduction in replicative lifespan following chronological aging in yeast

Abstract: Chronological and replicative aging have been studied in yeast as alternative paradigms for post-mitotic and mitotic aging, respectively. It has been known for more than a decade that cells of the S288C background aged chronologically in rich medium have reduced replicative lifespan relative to chronologically young cells. Here we report replication of this observation in the diploid BY4743 strain background. We further show that the reduction in replicative lifespan from chronological aging is accelerated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 57 publications
4
62
1
Order By: Relevance
“…This is consistent with a recent report that in chronological aging experiments performed in 2% glucose SC medium, cells that die in stationary phase exhibit a progressively larger DNA content at later time points. 13 It is not consistent with the argument based on the relatively small fraction of budded due to a deficiency in threonine that likely leads to the depletion of dNTP pools (Fig. 4).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This is consistent with a recent report that in chronological aging experiments performed in 2% glucose SC medium, cells that die in stationary phase exhibit a progressively larger DNA content at later time points. 13 It is not consistent with the argument based on the relatively small fraction of budded due to a deficiency in threonine that likely leads to the depletion of dNTP pools (Fig. 4).…”
Section: Discussionmentioning
confidence: 61%
“…This is suggested by the observations that buffering the medium to maintain a higher pH or the use of YPD medium-which also maintains a higher pH-reduces the fraction of stationary phase cells that are budded 10,13,22 as well as the number of dead cells harboring an S phase content of DNA. 13 Although, in contrast to W303 cells, the senescence and death of stationary phase BY4741 cells under these conditions is not due to limiting RNR1 expression, many other genes required for efficient DNA replication are also downregulated as cells transition into stationary phase; presumably, the product of a replicationrelated gene other than RNR1 becomes limiting in this strain background. In 10% glucose medium, sustained signaling by residual glucose is likely responsible for the increased fraction of cells that enter S phase from stationary phase.…”
Section: Discussionmentioning
confidence: 99%
“…There is also overlap between the various downstream components of DR. For example, inhibition of mTOR or Sch9 increases mitochondrial respiration and also induces stress response transcription factors that can enhance resistance to acidification-induced cell death (Bonawitz et al, 2007; Fabrizio et al, 2001; Lavoie and Whiteway, 2008; Pedruzzi et al, 2003). In addition, chronological aging leads to reduced RLS (Ashrafi et al, 1999; Delaney et al, 2013; Murakami et al, 2012), suggesting underlying mechanistic similarities between mitotic and post-mitotic lifespan within the same eukaryotic cell.…”
Section: Dietary Restriction In S Cerevisiaementioning
confidence: 99%
“…In several studies, formation of a population of very small cells was observed after glucose depletion (Aragon et al 2008; Murakami et al 2012; Volejnikova et al 2012; Li et al 2013). Li et al (2013) hypothesized that this population consisted of daughter cells which would eventually give rise to a Q-cell lineage.…”
Section: Introductionmentioning
confidence: 99%